P299 A clinicomycological study of suspected mucormycosis in post-COVID patients attending a tertiary care hospital. (20th September 2022) - Tak, Kiran; Rastogi, Vijaylatha; Verma, Pushpanjali; Gehlot, Vikas; Gupta, Mansi; Rawat, Digvijay; Prajapati, Shailja; Parihar, Geeta
Abstract: Poster session 2, September 22, 2022, 12:30 PM - 1:30 PM:   Objective: To study the fungal etiology, clinical, and epidemiological profile of suspected mucormycosis in post-COVID patients. Methods: A prospective observational study was undertaken over a period of 10 months from March to December 2021. A total of 175 biopsy samples were collected from 150 suspected cases of post-COVID mucormycosis patients in sterile normal saline at the ENT department and received in the department of microbiology. MRI of brain, orbital, and paranasal sinus was done in all patients. Tissue specimens were examined by direct KOH mount and cultures were inoculated on SDA with chloramphenicol and incubated at 22°C and 37°C for a minimum of 3-5 days and up to 4 weeks before declaring negative. The cultures were identified based on standard mycological protocols. Results: The prevalence of mucormycosis laboratory confirmed was found to be 42.66%. Out of 150 patients, 47 were KOH positive while 33 were culture positive. The most common isolate was Rhizopus arrhizus (84.85%) followed by R.microsporus var. rhizopodiformis (9.09%), Rhizomucor pusillus (3.03%), and Saksenaea vasiformis (3.03%). Rhino-orbital-cerebral mycormycosis was the most common clinical form (33 cases). Diabetes mellitus was the most common predisposing factor n  = 112 (74.66%). Many patients had multiple symptoms like periorbital swelling (52%), headache (44.7%), fever (41.3%), loss of vision (16%), facial swelling (27.3%), and nasal pain (8.7%). Invasive fungal sinusitis was seen in MRI in 116 (77.33%) cases. Tissue debridement was done in all positive patients along with treatment with liposomal amphotericin B (1.5-5.0 mg/kg/d) and then switched over to oral posaconazole 300 mg BD on the first day then 300 mg OD for several weeks. Inspite of rigorous treatment in 4.6% cases the prognosis was not good resulting in mortality. Also, in 40% of the patients who recovered, long-term morbidity related to vision was observed. Conclusion: Present study determined the fungal etiology of post covid mucormycosis with R. arrhizus being the most common cause in our region compared to other studies from India. The identification of risk factors, clinical features, and laboratory findings helped in early diagnosis, leading to prompt treatment, and favorable outcomes. With diabetes mellitus being the most common predisposing factor seen, it is suggested that a holistic approach to prevent, revert and treat this condition needs to be strengthened.